The totally unscientific study of the search for human happiness [compact disc, unabridged] - Poundstone, Paula (HighBridge, a division of Recorded Books, 2017)
The comedienne conducts a series of irreverent "scientific" experiments to discover the secret to happiness, from learning martial arts and speeding in a Lamborghini to communing with nature and volunteering.